The Influence Of Product Availability Related To Quality, Delivery, And Information Related To Complaints On Customer Satisfaction In An Indonesian E-Commerce Company (Case Study Of Shopee Express) - Arif Kuswanto; Muhammad Farrell Daiva (SEAN Institute, 2024)
This research discusses Shopee Express, a goods delivery service provided by Shopee. This service specializes in the field of goods delivery services. However, there are several problems faced by Shopee Express, related to product availability relate to quality, namely Shopee Express consumers complaining that the goods they received were damaged or even lost, as well as problems related to delivery, namely delays in delivery and complaints related to information relate to complaints, namely handling information that was not responded to by Shopee Express. This research adopts quantitative methods that include descriptive analysis and double linear regression. The study used the Indonesian population using the Shopee app and Shopee Express delivery services. The study applies quantitative research methods, which involve descriptive analysis and double linear regression. 385 using the measurement scale that is the ordinal scale. Data collected using SPSS version of Statistics 7. This study showed results that product availability related to quality is in the good category with a percentage of 70,5%, delivery in good category With a percent of 71.4%, information related to complaints related to information in the complaint category in both 69.9% and customer satisfaction of good category Based on the results of partial research, product availability related to quality, delivery, and complaint-related information has a positive as well as significant impact on customer satisfaction. Simultaneously the availability of products related to quality, delivery, information related to complaints has a positive as well as significant stake on customer satisfaction.